The Analysis of Social and Economic Potential of Central and Eastern European Economies - Arkadiusz NIEDZWIECKI; Marek PRONIEWSKI (Communications of International Proceedings, 2025)
This analysis is a voice in the public and scientific discussion on the economic potential of Central and Eastern European economies, in particular the ones belonging to the European Union. The research method used in the study is based on a linear ordering. The analysis covered variables that characterise multi-aspect development processes. As a result of the study, an order of economies according to a synthetic development index has been established. In a sense, this research may be seen as a complement to the European Commission analyses.
Keywords: Central and Eastern European; social and economic potential; linear ordering